1983
DOI: 10.1111/j.1365-2230.1983.tb01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet irradiation of human body sites in relation to occupation and outdoor activity: field studies using personal UVR dosimeters

Abstract: By use of personal dosimeters iticorporating polysulphone film, the proportions of ambient UVR received at several anatomical sites have been investigated in five occupations and nine outdoor recreational activities. The results suggested that both environmental and behavioural factors were of importance in determining overall levels of exposure and distribution by site. A closer examination of the risks of skin cancers associated with UVR exposure in humans should be possible in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 8 publications
10
124
2
1
Order By: Relevance
“…9, 10, 12 Using the same analysis for shoulder and wrist dosimeters, we found that the shoulder received significantly higher UVER exposure, in agreement with other studies on outdoor activities. 36,37 If we considerer the solar height, UVER exposure received by all children in the S.H. 1 period is significantly lower than that received in the other two periods.…”
Section: Discussionmentioning
confidence: 99%
“…9, 10, 12 Using the same analysis for shoulder and wrist dosimeters, we found that the shoulder received significantly higher UVER exposure, in agreement with other studies on outdoor activities. 36,37 If we considerer the solar height, UVER exposure received by all children in the S.H. 1 period is significantly lower than that received in the other two periods.…”
Section: Discussionmentioning
confidence: 99%
“…Both manikins were rotated clockwise by ninety degrees every 15 minutes to minimise any directional effects, such as over exposure to one site, and also to replicate the effect of human random orientation to the sun when outdoors. Previous comparisons of the UV received by rotating manikins and humans undertaking normal outdoor activities have shown that the UV exposures to the manikin cheek, hand and thigh provide a good approximation of the UV exposures to these sites on humans [16]. The manikin UV measurements overestimate the exposures to the shoulder and sternum and underestimate the exposure to the lumbar spine and upper arm, probably due to a tendency of humans to stoop forward and outstretch the arms and a preference to turn away from the direct sun.…”
Section: Uv Exposure Distributionmentioning
confidence: 99%
“…Since the 1970s, some studies have measured sun exposure during selected activities such as gardening or walking (7,8,9,10,11).Others have focussed on measuring personal solar UVR exposure to generate baseline exposures in different population groups and behavioural settings (12,13). There have also been a few longitudinal studies concerning child sun exposure (14,15,16).…”
Section: Introductionmentioning
confidence: 99%